Romans disarmed resisting empire, demanding justice - Keesmaat, Sylvia C.; Walsh, Brian J. 1953- (Grand Rapids Brazos Press, 2019)
Helps readers enter the world of ancient Rome and see how Paul's most radical letter transforms the lives of the most marginalized then and now.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books